Biodiversity buffers the impact of eutrophication on ecosystem functioning of submerged macrophytes on the Yunnan-Guizhou Plateau, Southwest China. (1st December 2022) - Wang, Hao; Zhang, Xiaolin; Shan, Hang; Chaochao lv; Ren, Wenjing; Wen, Zihao; Tian, Yuqing; Weigel, Benjamin; Ni, Leyi; Cao, Te
Abstract: Increasing eutrophication poses a considerable threat to freshwater ecosystems, which are closely associated with human well-being. As important functional entities for freshwater ecosystems, submerged macrophytes have suffered rapidly decline with eutrophication. However, it is unclear whether and how submerged macrophytes maintain their ecological functions under increasing eutrophication stress and the underlying patterns in the process. In the current study, we conducted an extensive survey of submerged macrophytes in 49 lakes and reservoirs (67% of them are eutrophic) on the Yunnan-Guizhou Plateau of southwestern China to reveal the relationship between submerged macrophyte biodiversity and ecosystem functioning (BEF) under eutrophication stress. Results showed that submerged macrophytes species richness, functional diversity (FD), and β diversity had positive effects on ecosystem functioning, even under eutrophication. Functional diversity was a stronger predictor of community biomass than species richness and β diversity, while species richness explained higher coverage variability than FD and β diversity. This suggests that species richness was a reliable indicator when valid functional traits cannot be collected in considering specific ecological process. With increasing eutrophication in water bodies, the mechanisms underlying biodiversity-ecosystem functioning evolved from "niche complementarity" to "selection effects", as evidenced by decreased species turnover and increased nestedness. Furthermore, the relative growth rate, specific leaf area, and ramet size in trade-off of community functional composition became smaller along eutrophication while flowering duration and shoot height became longer. This study contributes to a better understanding of positive BEF in freshwater ecosystems, despite increasing anthropogenic impacts. Protecting the environment remained the effective way to protect biodiversity and corresponding ecological functions and services. It will be important to consider different facets of biodiversity on ecosystem functioning in future studies to improve effective management plans. Graphical abstract: Image 1 Highlights: Positive BEF relationship for submerged macrophytes even under eutrophication stress. Functional diversity had highest predictive power for ecosystem processes. Shifting strategies of macrophyte communities to adapt to eutrophication.